Facilitating access to the renal transplant waiting list does not increase the number of transplantations: comparative study of two French regions - Lefort, Mathilde (Clin Kidney J, 2016)
BACKGROUND: In France, there are important regional disparities of access to the renal transplant waiting list and transplantation. Our objectives were to compare the characteristics of patients with end-stage renal disease (ESRD) of two French regions (Ile-de-France and Bretagne) and to identify determinants of access to the waiting list and subsequent transplantation, with a focus on temporary inactive status (TIS) periods. METHODS: All 18–80-year-old incident patients who started dialysis in Ile-de-France or Bretagne between 2006 and 2009 were included (n = 6160). Associations between patients' characteristics and placement on the waiting list or transplantation were assessed using a Fine and Gray model to take into account the competing risk of death and living donor transplantation. RESULTS: At the end of the follow-up (31 December 2013), more patients had undergone transplantation in Bretagne than in Ile-de-France (30 versus 27%), although the percentage of waitlisted patients was higher in Ile-de-France than in Bretagne (47 versus 33%). More patients were on TIS and with a longer median TIS duration in Ile-de-France. Independent of age and clinical characteristics, patients in Bretagne were less likely to be waitlisted than those in Ile-de-France [subdistribution hazard ratio 0.77 (95% confidence interval 0.7–0.9)]. After waitlisting, patients in Bretagne were four times more likely to be transplanted. CONCLUSIONS: Our study highlights clinical practice differences in Bretagne and Ile-de-France and shows that facilitating access to the waiting list is not sufficient to improve access to renal transplantation, which also depends on organ availability.